Studies on the genus Mesandrothrips from China, with a new species (Thysanoptera: Phlaeothripinae: Haplothripini) - Dang, Li-Hong; Zhao, Lin-Peng; Xie, Dan-Le; Zhao, Le; Qiao, Ge-Xia (Zootaxa, 2020)
In the recently re-instated genus Mesandrothrips Priesner, four species are recognized from China, and an illustrated key is provided here. This includes one new species, M. acutisetis sp.n., together with the first record of M. subterraneus from China.